Investigating the determinants and growth of financial technology depth of penetration among the heterogeneous Africa economies - Tochukwu Timothy Okoli; Devi D. Tewari (Cogent Economics & Finance, 2020)
The widespread financial exclusion in Africa despite the continent's high adoption of financial technology (Fintech) suggests that there is a gap between Fintech's adoption and its actual usefulness. This study seeks to measure Fintech's usefulness, its growth and identify its determinants in a panel of three emerging, twenty-four frontiers and five fragile African markets for the period 2004-2018. A dummy variable interactive equation was modelled based on theory to account for heterogeneity between groups. Results from the system Generalised Method of Moments (GMM) estimation technique reveal that on average, Fintech usefulness in Africa is a dynamic heterogeneous process. Income per person, level of financial development, Fintechs' compatibility with users' experiences, users' risk perception, inflation rate and financial-openness were the main determinants of its usefulness. Its rapid growth after the 2009 financial crisis suggests that greater Fintech usefulness can mitigate financial crisis among Africa markets. In particular, the growth of Mobile-banking, ATM and Internet-banking as at 2018 are on average 41.8%, 0.4%, and 20.8% respectively greater than its average in the base year 2004. The study concludes that Fintech's usefulness is driven by economic, financial and psychological factors; therefore, structural transformation, financial development and improved literacy were recommended.
Keywords: G00; G21; G24; O55; 330; African economies; ATM; financial technology; internet banking; mobile banking